1981
DOI: 10.1007/bf02342545
|View full text |Cite
|
Sign up to set email alerts
|

Linkage relationships between genes controlling seed proteins in French bean

Abstract: The inheritance of phaseolin and globulin-2 (G2)/albumin polypeptides was investigated in crosses involving varieties which exhibited the three electrophoretic banding patterns of phaseolin found in French bean. 'Total' seed protein extracts of single seeds of the F1 and F2 generations from the crosses: 'Sanilac' × 'Contender', 'BBL 240' × 'Contender', and 'Sanilac' × 'BBL 240' were analyzed by two-dimensional electrophoresis. Segregation of the genes controlling phaseolin and G2/albumin polypeptides, and thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(34 citation statements)
references
References 27 publications
(58 reference statements)
1
33
0
Order By: Relevance
“…However, genetic linkage of the multigene family of the Phaseolus seed lectins has been reported (Brown et al 1981;Hoffman and Donaldson 1985). In addition, proteins such as ribulose bisphosphate carboxylase, actin, and leghemoglobin are coded by small families of genes, and usually at least a portion of the genes within the family is tightly linked.…”
Section: Discussionmentioning
confidence: 99%
“…However, genetic linkage of the multigene family of the Phaseolus seed lectins has been reported (Brown et al 1981;Hoffman and Donaldson 1985). In addition, proteins such as ribulose bisphosphate carboxylase, actin, and leghemoglobin are coded by small families of genes, and usually at least a portion of the genes within the family is tightly linked.…”
Section: Discussionmentioning
confidence: 99%
“…The banding patterns obtained by single and two-dimensional gel electrophoretic analyses, indicate that Contender is a composite of Tendergreen and Sanilac types, showing a good agreement between the number of phaseolin protomers and structural genes. Genetic analysis revealed a tight linkage for the entire phaseolin gene family [17]. Heteroduplex analysis of the phaseolin genomic clones [36] revealed that whereas the phaseolin DNA coding sequences were similar, considerable divergence occurred close to their 5' and 3' termini [37].…”
Section: Phaseolin Gene Structurementioning
confidence: 98%
“…The ability to obtain large quantities of purified phaseolin facilitated electrophoretic studies using one dimensional SDS gels [12] and characterization by equilibrium sedimentation [13]. These initial forays paved the way for biophysical characterization [14][15][16][17] and the subsequent crystallographic structural analysis [18][19][20][21].…”
Section: Phaseolin -The Early Yearsmentioning
confidence: 99%
“…Common bean contains higher levels of protein (>20%) compared to cereals such as rice and wheat (<15%) (Kaplan, 1965;Brown et al, 1981a;Chandrakanth and Hall, 2008). Phaseolin, a protein mainly stored in seeds, makes up the majority of total seed protein.…”
Section: Introductionmentioning
confidence: 99%
“…Type "B" phaseolin is present only in wild and cultivated varieties of Colombia. Such variety in phaseolin types is thought to have resulted from random outcrosses in nature, contaminations from cultivation areas and multiple cultivation efforts (Brown et al, 1981a;Koenig et al, 1990;Kami et al, 1995).…”
Section: Introductionmentioning
confidence: 99%